Entry, standards and competition: Firm strategies and the diffusion of mobile telephony - Heli Koski; Tobias Kretschmer (The Research Institute of the Finnish Economy (ETLA), 2002)
This paper focuses on the effects of within and between standards competition and competition between firms on the performance of an emerging new technology, digital mobile telecommunication (2G). Our empirical exploration provides a more complete picture of the market dynamics of digital mobile telephony than the previous studies that have typically estimated econometric models that ignore the role of endogenous decisions of service providers in the observed market behaviour. The incorporation of endogenous supply side decisions regarding market entry and pricing to the model explaining the diffusion of digital mobile telephony allows us to distinguish the effects of within-standard and within-firm competition on the observed diffusion phenomenon. We use data from 32 industrialized countries over the 1992–99 time period. It appears that incorporating the timing of market entry to the econometric model explaining 2G diffusion and service prices is, indeed, critically important. Controlling for entry provides more accurate estimates of the coefficients of the explanatory variables and also affects conclusions to be made concerning the policy variables of our interest. Our major finding is that cross-country differences in within and between standards competition and competition between firms have greatly influenced 2G diffusion patterns and service prices. Standardization has clearly facilitated diffusion of digital mobile phones. Nevertheless, it is also positively related to wireless service prices. Between standards competition apparently triggers more aggressive price competition than competition that takes places within a single standard. Our empirical investigation further suggests that consumers in the countries that have been relatively more advanced in liberalizing the market for telecommunication services have not only benefited from the earlier launch of digital mobile services but also from competition in the wireless service provision resulting in lower digital mobile service prices and greater 2G diffusion. Service price have been affected by competition particularly when there have been at least two entrants at the time of introduction of 2G services. The monopolistic position of early entrants, instead, has lead to less aggressive pricing strategies. – competition ; standardization ; diffusion ; pricing ; mobile telephony
Keywords: L1; L5; O3; 330; Wettbewerb; Normung; Innovationsdiffusion; Preis; Mobiltelefon